2014
DOI: 10.1016/j.pain.2014.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of RVM-expressed P2X7 receptor in bone cancer pain: Mechanism of descending facilitation

Abstract: Patients with bone cancer commonly experience bone pain that is severe, intolerable, and difficult to manage. The rostral ventromedial medulla (RVM) plays an important role in the development of chronic pain via descending facilitation of spinal nociception. The compelling evidence shows that glial P2X7 receptor (P2X7R) is involved in the induction and maintenance of chronic pain syndromes. The present study explored the mechanism of glial activation and P2X7R expression underlying the induction of bone cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 44 publications
2
46
1
Order By: Relevance
“…While all the existing studies using this model typically assess the pain behaviors only until around 20–25 days after injection of cancer cells, our findings are the first to successfully investigate the model for up to 66 days and to show that W256 cell-induced bone pain can apparently resolve spontaneously at later stages despite the ongoing presence of cancer cells, similar to the clinical situation in humans. The beginning of resolution of pain hypersensitivity behavior around 20–25 days after surgery in this model has been observed in other studies, although these studies only assessed pain behaviors until 20–25 days (Zhao et al, 2010; Xu et al, 2013; Huang et al, 2014). A similar spontaneous reversal of mechanical hypersensitivity has been reported in rats administered a unilateral ITI of MRMT-1 cells in a BCIBP model (Falk et al, 2015).…”
Section: Discussionsupporting
confidence: 62%
“…While all the existing studies using this model typically assess the pain behaviors only until around 20–25 days after injection of cancer cells, our findings are the first to successfully investigate the model for up to 66 days and to show that W256 cell-induced bone pain can apparently resolve spontaneously at later stages despite the ongoing presence of cancer cells, similar to the clinical situation in humans. The beginning of resolution of pain hypersensitivity behavior around 20–25 days after surgery in this model has been observed in other studies, although these studies only assessed pain behaviors until 20–25 days (Zhao et al, 2010; Xu et al, 2013; Huang et al, 2014). A similar spontaneous reversal of mechanical hypersensitivity has been reported in rats administered a unilateral ITI of MRMT-1 cells in a BCIBP model (Falk et al, 2015).…”
Section: Discussionsupporting
confidence: 62%
“…), and cancer pain (Huang et al . ) has been suggested previously. Consistently, here we showed that descending facilitation was also involved in the development of CPSP.…”
Section: Discussionmentioning
confidence: 55%
“…) or during cancer development (Huang et al . ). The ATP‐gated P2X7 receptor (P2X7R) is predominantly present on microglia in the central nervous system.…”
mentioning
confidence: 97%
“…Thus, the verification of tibial tumor burden post-mortem is very important. However, the beginning of pain behavior resolution at 20–25 days post-surgery is typically not due to tumor regression, but may involve neuro-immune mechanisms (Zhao et al, 2010; Xu et al, 2013; Huang et al, 2014). In previous work by others using different cancer cell lines, up regulation of the endogenous opioid system is implicated in spontaneous pain behavior resolution (Muralidharan et al, 2013).…”
Section: Regression Of Tumor and Resolution Of Painmentioning
confidence: 99%